Pain management associated with surgery on the tonsils (Pain medicine, 2017)
Surgery on the palatine tonsils is one of the most common surgical procedures in the world. Any surgical intervention is a serious manipulation that cannot be considered separately from the preparation and postoperative period, since the patient’s state of health and the effectiveness of the intervention depend on the overall approach to managing the patient. Pain and PONV (postoperative nausea and vomiting) often accompany the operated person, these delay the beginning of rehydration of the patient, as well as intake of food. To mitigate these symptoms, a large number of manipulations have been proposed, which take place since preoperative preparation.Goal.To identify (from a variety of techniques that should reduce the pain) those which have demonstrated efficacy in randomized placebo-controlled studies (RPCS) and systematic reviews, that means, that their effectiveness is proven in terms of evidence-based medicine.Results.A lower level of pain is observed in patients with partially removed palatine tonsils. Also effective were the following options for exposure: intraoperative administration of dexamethasone, the use of antiemetics (cyclizine, dolasentron, granisetron, metoclopramide, ondasetron and troposetron), NSAIDs (ibuprofen) and paracetamol, acupuncture stimulation of the wrist point P6.
Keywords: tonsillitis; tonsilotomy; tonsillectomy; pain